Managing foreign exchange risk : strategies for global portfolios - DeRosa, David F. (London; New York : McGraw Hill, 1991)
The past decade has witnessed the rapid introduction and the widespread use of the new and complex financial instruments and hedging strategies by banking, investment and treasury and finance professionals around the world to control and minimize the foreign exchange risks associated with their institutional securities. This book provides an analysis of some of these developments.
Includes bibliographical references (p. 223-227) and index.
rpm 20/09/2016
Loans
Keywords: Foreign exchange; Risk management; Investments, Foreign; Foreign exchange futures; Hedging (Finance); Swaps (Finance); Options (Finance)